Legal Status of Flat Unit Ownership Certificate (Strata Title) in Indonesia (Italian Review of Legal History, 2020)
This study seeks to examine the legal status of flat unit ownership rights between Law Number 5 of 1960 and Law Number 20 of 2011; by using normative legal research (statute approach and concept approach), this research concludes: the legal status of flat unit ownership certificate as stipulated in the Law Number 5 of 1960 and Law Number 20 of 2011 cannot be said to have a conflict of legal norms. The difference in interpretation of those laws can be resolved by: (1) The principle of lex specialis derogat lex generale, means specific laws (in this case is Law Number 20 of 2011 concerning Flats) overrides general laws (in this case is Law Number 5 of 1960 concerning Basic Agrarian Law); (2) Article 16 paragraph (1) letter h of Law Number 5 of 1960 concerning Basic Agrarian Law provides: other rights not included in the previously mentioned rights will be stipulated in the law, as well as the temporary rights as referred to in article 53; thus, the term flat unit ownership certificate can be accepted because it does not conflict with applicable laws and regulations.
Keywords: Legal Status; Flat Unit Ownership Certificate; legal research; Conflict.